2024
DOI: 10.1101/2024.03.26.586350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of gliomas DNA methylation: Assessment of pre-analytical variables

Karol Bomsztyk,
Daniel Mar,
Oleg Denisenko
et al.

Abstract: Precision oncology is driven by molecular biomarkers. For glioblastoma multiforme (GBM), the most common malignant adult primary brain tumor, O6-methylguanine-DNA methyltransferase (MGMT) gene DNA promoter methylation is an important prognostic and treatment clinical biomarker. Time consuming pre-analytical steps such as biospecimen storage before fixing, sampling, and processing are major sources of errors and batch effects, that are further confounded by intra-tumor heterogeneity of MGMT promoter methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Although many neuropathology practices do not routinely re-test MGMT promoter methylation at recurrence or in multiple regions during surgery, recent reports have indicated that among other genetic and epigenetic changes, there may be spatial and/or temporal differences in MGMT promoter methylation status (Fig. 4 a), particularly after treatment with TMZ [ 17 , 23 , 58 , 61 , 78 , 133 , 156 , 165 , 225 ]. There may be significant epigenetic heterogeneity at this particular locus, and progression from hypermethylated to hypomethylated MGMT promoter status in recurrent tumors may reflect the selection of existing hypomethylated MGMT cells and serve as a mechanism for further resistance to TMZ [ 25 , 156 ].…”
Section: Epigenetic Plasticity Epigenetic Instability the G-cimp Phen...mentioning
confidence: 99%
“…Although many neuropathology practices do not routinely re-test MGMT promoter methylation at recurrence or in multiple regions during surgery, recent reports have indicated that among other genetic and epigenetic changes, there may be spatial and/or temporal differences in MGMT promoter methylation status (Fig. 4 a), particularly after treatment with TMZ [ 17 , 23 , 58 , 61 , 78 , 133 , 156 , 165 , 225 ]. There may be significant epigenetic heterogeneity at this particular locus, and progression from hypermethylated to hypomethylated MGMT promoter status in recurrent tumors may reflect the selection of existing hypomethylated MGMT cells and serve as a mechanism for further resistance to TMZ [ 25 , 156 ].…”
Section: Epigenetic Plasticity Epigenetic Instability the G-cimp Phen...mentioning
confidence: 99%